Persistent Gestational Trophoblastic Neoplasia (PTN) (Journal of Dhaka National Medical College & Hospital, 2015)
A 35-year old lady had persistent Gestational Trophoblastic  Neoplasia following  molar pregnancy. Initially the patient came with hydatidiform mole diagnosed by trans abdominal ultrasonography and high level of serum β-hCG. At that time patient was treated by suction & evacuation of molar tissues. After evacuation serum B- hCG level declined but not reached to normal level. During follow-up period patient complained of irregular per-vaginal bleeding & her β-hCG level again rised & ultrasonology showed-some molar tissues within the endometrium. She was diagnosed as a case of persistent trophoblastic neoplasia(PTN). We then gave her two courses of systemic Methotrexate(MTx) therapy and patient’s serum B hCG level return back to normal.A persistent trophoblastic disease can be successfully treated with systemic Methotrexate  therapy.J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 58-60